Use of saline water for irrigation - J Rhoades (California Agriculture, 1984)
Not available – first paragraph follows: Expansion of irrigated agriculture would contribute significantly toward meeting world food and fiber needs but, at the same time, would run headlong into competition for ever more limited water supplies. By reassessing the criteria for suitability of water (and land) for irrigation, however, available supplies can be expanded significantly. Very conservative standards have been used in the past. If these standards are relaxed, water generally classified as too saline for irrigation can often be used successfully without hazardous long-term consequences to crops or soils, even under conventional farming practices. Adoption of new crop and water management strategies would further facilitate the use of saline waters for irrigation and could make possible a sizable expansion of irrigated agriculture.